2019
DOI: 10.1109/tit.2019.2898660
|View full text |Cite
|
Sign up to set email alerts
|

Centralized Multi-Node Repair Regenerating Codes

Abstract: In a distributed storage system, recovering from multiple failures is a critical and frequent task that is crucial for maintaining the system's reliability and fault-tolerance. In this work, we focus on the problem of repairing multiple failures in a centralized way, which can be desirable in many data storage configurations, and we show that a significant repair traffic reduction is possible. First, the fundamental tradeoff between the repair bandwidth and the storage size for functional repair is established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 56 publications
(157 reference statements)
0
20
0
Order By: Relevance
“…Therefore, we transmit 100 symbols in F 1 , which can be normalized to b (n−1)ℓ = 0.4545. Compared with the scheme in [16], which need ℓ = 2.4 × 10 19 and b (n−1)ℓ = 0.25, we provide a tradeoff between ℓ and b. It should be noted that in this example, the RS(12, 8) code needs to be extended from an RS(3, −1) code, which does not exist.…”
Section: Schemes In Multiple Cosetsmentioning
confidence: 99%
“…Therefore, we transmit 100 symbols in F 1 , which can be normalized to b (n−1)ℓ = 0.4545. Compared with the scheme in [16], which need ℓ = 2.4 × 10 19 and b (n−1)ℓ = 0.25, we provide a tradeoff between ℓ and b. It should be noted that in this example, the RS(12, 8) code needs to be extended from an RS(3, −1) code, which does not exist.…”
Section: Schemes In Multiple Cosetsmentioning
confidence: 99%
“…The next theorem shows that the repair bandwidth for multiple failures can be further reduced in the centralized repair setting [4], [18], by a sequential repair mechanism, and exploiting the repair symbols contributed by already repaired failed nodes which can act as helpers.…”
Section: Resultsmentioning
confidence: 99%
“…This requires a repair bandwidth from each helper node that scales linearly with the number of failures. There are two types of repair for multiple failures studied in the literature [18]: (i) centralized regenerating codes and (ii) cooperative regenerating codes. In centralized regenerating codes, a single data center is responsible for the repair of all failed nodes.…”
Section: B Multiple Failures Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…In[31], it was shown that for e 2, when k is a multiple of e,β MBCR =β MBMR ,ᾱ MBCR >ᾱ MBMR ; otherwise, β MBCR >β MBMR .Zorgui M, et al Sci China Inf Sci…”
mentioning
confidence: 99%